THE IMPORTANCE OF DIVERSIFYING THE USE OF SOME MODERN TEACHING METHODS IN IMPROVING SOME PHYSICAL QUALITIES IN THE LONG JUMP - Harbach Ibrahim,; Djerdem Ben Dhiba,; Mokrani Djamel, (Sport Scientific And Practical Aspects, 2025)
The purpose of this study is to understand the importance of the diversification of some modern teaching methods to improve some physical attributes of long jump speed, in order to know the most effective methods in long jump. To achieve the main objective, the researchers used the experimental method. Thirty male students of 18 to 22 years old, were randomly selected to study at the Institute of Physical Education and sports of Mostaganem. They divided into a pilot sample and a control sample.The researchers concluded that the use of several teaching methods in the physical education and sport lesson had a positive effect to improving physical performance in long jump.